Komitmen Identitas Etnik dalam Kaitannya dengan Eksistensi Budaya Lokal - Tarakanita, Irene; Cahyono, Maria Yuni Megarini (Zenit, 2013)
Indonesia is an archipelago with approximately 1,128 races and cultural diversity. Each race contributes itself to the local distinctiveness in terms of custom, language, architecture, music, dance, decoration, fashion, food, and others. History shows how the local arts of the past were able to adapt themselves to the arts from outside as well as transform the local culture in Indonesia, and has produced many stunning works of art in the forms of prehistoric art, classical and traditional art. The values of life in the tribal society rely on the  wisdom of the natural environment, which is a source of cultural wealth of a nation that needs to be maintained and preserved. Indonesia is a big challenge for artists to be able to create works of art that has the characteristics or character in his wor. The method of  this research is descriptive, while the statistical test uses Spearman Rank correlation coefficient. The measuring instrument is used to measure the ethnic identity in the forms of questionnaire, and translation from Multiple Ethnic Identity Measure (MEIM). Measurement  was done for the entire population of 200 students. Based on the statistical data processing, 15.5% of the students are at the stage of Achieved, 71% at the  stage of Examined, and 13.5% at the stage of Unexamined. Based on ethnic background of each student, variations of ethnic identity views were found among the first year students in